Glycosylated ovine prolactin. - Lewis, U J (1984)
A modification of prolactin, in which the asparagine at position 31 carries a carbohydrate unit, was isolated from ovine pituitary glands. Sequence and amino acid analyses identified the point of linkage of the carbohydrate. Glucosamine was found in acid hydrolysates, an indication that the carbohydrate is attached through N-acetylglucosamine. The glycosylated prolactin binds to concanavalin A and lentil lectin and is eluted with methyl alpha-D-mannopyranoside. During gel electrophoresis in sodium dodecyl sulfate, the glycosylated hormone migrates as a Mr 25,000 protein; prolactin has a Mr of 23,000. The modified prolactin had a potency of 20 international units/mg, approximately equal to 60% the potency of a reference prolactin preparation when measured by the pigeon crop sac assay. In a radioimmunoassay, the glycosylated form had only 34% the immunoreactivity of ovine prolactin.